2006
DOI: 10.1002/eat.20201
|View full text |Cite
|
Sign up to set email alerts
|

Who is Providing what Type of Psychotherapy to Eating Disorder Clients? A Survey

Abstract: Objective: Little is known about the psychotherapies delivered to eating-disordered clients by community therapists. We sought to describe the education and training of psychotherapists working with eating-disordered clients, the psychotherapeutic approaches used, and the reasons for use.Method: Eligible Calgary clinicians were identified and asked to complete a 25-item telephone interview.Results: The response rate was 74%. Educational backgrounds and fields of specialization of clinicians who completed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 15 publications
6
52
1
Order By: Relevance
“…They described the most important influence on their work as their own past clinical experiences: They strongly to moderately agree that past clinical experiences affect their treatment decisions, and indicated that they usually use past experiences with patients to improve therapy skills and effectiveness. That clinicians prefer to rely on clinical experience rather than EST research to inform treatment decisions is consistent with much of the prior research in the field (Morrow-Bradley & Elliott, 1986;Raine et al, 2004;von Ranson & Robinson, 2006). However, it is inconsistent with the thrust of EBP, which emphasizes the use of research to guide practice, albeit tempered by the therapist's clinical expertise (Straus et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…They described the most important influence on their work as their own past clinical experiences: They strongly to moderately agree that past clinical experiences affect their treatment decisions, and indicated that they usually use past experiences with patients to improve therapy skills and effectiveness. That clinicians prefer to rely on clinical experience rather than EST research to inform treatment decisions is consistent with much of the prior research in the field (Morrow-Bradley & Elliott, 1986;Raine et al, 2004;von Ranson & Robinson, 2006). However, it is inconsistent with the thrust of EBP, which emphasizes the use of research to guide practice, albeit tempered by the therapist's clinical expertise (Straus et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…In a survey of 591 psychologists in independent practice, clinicians described their clinical experiences as having the greatest impact on their treatment decisions, an impact significantly greater than that of research evidence (Stewart & Chambless, 2007). In a telephone survey of 52 clinicians who treat eating disorders, von Ranson and Robinson (2006) found that clinicians' most common reason for selecting a particular therapeutic approach was that their clinical experience indicated the treatment was effective. Similarly, Raine et al (2004) found that clinicians were open to and accepting of research evidence only if it was supported by their experience in clinical practice.…”
Section: Theoretical Obstaclesmentioning
confidence: 97%
“…Earlier studies seem to suggest this. [9][10] The guidelines describe that the available evidence, particularly on treatment of BN and BED, shows the effectiveness of CBT on eating behaviors as well as on self-esteem and social functioning. However, therapists who are trained to work from other theoretical orientations, for instance, a psychodynamic or client-centered orientation, in which the alliance as a vehicle for change is a core feature of therapy may find working from a manual alienating.…”
Section: A Comparison Of Therapists and Patients On The Quality Of Trmentioning
confidence: 99%